HUBUNGAN ANTARA PEMENUHAN KEBUTUHAN SPIRITUAL DENGAN TINGKAT STATUS MENTAL PADA ORANG DENGAN GANGGUAN JIWA (ODGJ) - Kadek Verlyanita Septiarini; Ni Made Dian Sulistiowati; Desak Made Widyanthari (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
THE CORRELATION BETWEEN FULFILLMENT OF SPIRITUAL NEEDS AND MENTAL STATUS LEVEL IN PEOPLE WITH PSYCHIATRIC DISORDER (ODGJ) ABSTRACTThe fulfillment of spiritual needs was required by the people with Psychiatric Diorder (ODGJ), considering the spiritual needs are very important in the change of mental status. This study was aimed to finding out the correlation between Fulfillment of Spiritual Needs and Mental Status Level in people with Psychiatric Disorder (ODGJ) at Wilayah Kerja Puskesmas II Denpasar Timur. This was a quantitative study that applies cross -sectional method. The sample for this study is 69 respondents by using purposive sampling technique. The data are analyzed by using Spearman-Rho. The instruments which are used for collecting data of this study are a questionnaire about spiritual fulfillment and Mini Mental State Examination (MMSE) questionnaires.The results showed the number of loading spiritual needs either as much as 46 respondents or 66.7%. Meanwhile, most of the respondet has a high level of mental status that is 37 respondents or 53.6%. The result of the analysis shows that there is a correlation between fulfillment of spiritual needs and Mental Status Level on ODGJ with p value 0.000 with positive correlation 0,863 and positive direction. Based on the findings above, it is advisable to the nurse to make programs related to the spiritual such as routine joint prayer and ODGJ peguyuban which is spiritual meaning.